TRANSFORMASI DIGITAL PERAN AI DALAM KONSERVASI DAN RESTORASI BANGUNAN HERITAGE - Andi Abidah (Universitas Negeri Makassar, 2023)
The conservation and restoration of heritage buildings represent crucial challenges in preserving human cultural and historical wealth. In the current era of digital transformation, artificial intelligence (AI) has emerged as an innovative tool playing a pivotal role in supporting efforts to conserve and restore historical buildings. This paper explores the fundamental role of AI in the digital transformation of heritage building preservation. We review various AI technologies used in this context, such as sensor-based structural monitoring, pattern recognition for damage identification, and the utilization of 3D modeling algorithms for virtual restoration. Furthermore, we discuss the positive impact of AI in digitizing historical data and creating realistic simulations that facilitate better conservation decision-making. The research aims to examine the role of AI in heritage building conservation and restoration. The research methodology employs qualitative and literature review studies